Kecerdasan Emosional, Kompetensi Kepemimpinan Transformasional - Nurtantiono, Andri (STIE Surakarta, 2012)
Transformational leadership is the ability of leaders to motivate followers to reach beyond what is normally done. Competence or ability to realize ones own feelings, aware of the feelings of others, distinguish between them, and use information to guide ones thinking and behavior is the competence of Emotional Intelligence (Emotional Quotient / Emotional Intelligence). Emotional Intelligence is Intrapersonal dimension, as an indicator of self-awareness and self-expression, interpersonal used to measure the social awareness and interpersonal relationships, Stress Management is used for Management and Control of Emotion, Adaptation is used as an indicator of the ability to Managing Change, and General Mood is used as an indicator of Motivation self.